Pengaruh Teknik Asertif untuk Meningkatkan Keterbukaan Diri Siswa dalam Layanan Konseling Kelompok pada Siswa Kelas XI UPTD SMKN 1 Polewali - Ahmad Ahmad; Farida Aryani; Sahril Buchori (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
Self-disclosure is an individual’s ability to consciously express thoughts, feelings, experiences, and personal needs within social interactions. This ability is essential for students because it influences the quality of interpersonal relationships, emotional development, communication skills, and academic success in school. However, some students still experience difficulties in expressing themselves, resulting in passive behavior, low self-confidence, limited classroom participation, and communication barriers with peers and teachers. This study aims to identify the initial level of students’ self-disclosure, describe the implementation of assertive techniques in group counseling services, and analyze the effectiveness of these techniques in improving self-disclosure among Grade XI students at UPTD SMKN 1 Polewali. The study employs a quantitative approach using an experimental research method. The intervention is conducted through a series of structured group counseling sessions designed to train students to express their thoughts, feelings, opinions, and needs clearly, appropriately, confidently, and respectfully toward others. Data are collected through self-disclosure measurement instruments administered before and after the intervention to evaluate changes in students’ openness. The findings are expected to demonstrate that the application of assertive techniques in group counseling can significantly improve students’ self-disclosure, enhance their confidence in communicating, strengthen positive social interactions, and encourage more active participation in learning activities. Therefore, assertive group counseling can serve as an effective guidance and counseling strategy to support students’ personal, social, and academic development in the school environment.